Design and Development of Mechanical Structure and Control System for Tracked Trailing Mobile Robot - Rui Zhu; Jianxing Ren; Zhiwei Chen; Hongchuan Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Along with the science and technology unceasing progress, the uses of tracing robots become more and more widely. Tracked tracing robot was adopted as the research object in this paper, mechanical structure and control system of robot was designed and developmented. In mechanical structure design part, structure designed and positioned  were completed, including design of robot body, wheel, underpan, transmission structure and the positioning of batteries, control panel, sensors, etc, and then robot dynamics was analyzed; In control section, M30245 was used as the core, according to the characteristics of tracked tracing robot differential drive, realization scheme of motion control system was put forward, system drive circuit, detection module, control program were developed. System were discussed and checked through test. From this paper tracked tracing robot was researched, and a certain design and experimental basis can be provided in future research. DOI: http://dx.doi.org/10.11591/telkomnika.v11i2.1995